ByzRev 07.2025.072: Mark Edwards – Dimitrios Pallis – Georgios Steiris (eds), The Oxford Handbook of Dionysius the Areopagite (Oxford Handbooks). : Oxford: Oxford University Press 2022. - Turenko, Vitalii (The Byzantine Review, 2025)
Mark Edwards – Dimitrios Pallis – Georgios Steiris (eds), The Oxford Handbook of Dionysius the Areopagite (Oxford Handbooks). Oxford: Oxford University Press 2022. XIII, 729 pp. – ISBN 978-0-19-881079-7